2016
DOI: 10.1017/s204017441600043x
|View full text |Cite|
|
Sign up to set email alerts
|

Early inherited risk for anxiety moderates the association between fathers’ child-centered parenting and early social inhibition

Abstract: Studies of the role of the early environment in shaping children’s risk for anxiety problems have produced mixed results. It is possible that inconsistencies in previous findings result from a lack of consideration of a putative role for inherited influences moderators on the impact of early experiences. Early inherited influences not only contribute to vulnerabilities for anxiety problems throughout the lifespan, but can also modulate the ways that the early environment impacts child outcomes. In the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Parent sociability and offspring positive emotionality 110 , and parent behavioural motivation and offspring social motivation 61 shared common genetic factors, whereas the intergenerational transmission of neuroticism seemed to be environmentally explained 29 . There was no evidence of an environmental association between parental traits, including anxiety 111 , sociability 110 , and smoking during pregnancy 71 , and offspring personality traits such as sociability and temperament. In addition, an extended twin study found no evidence of environmental transmission or rGE underlying associations between parent and offspring dimensional personality traits 112 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Parent sociability and offspring positive emotionality 110 , and parent behavioural motivation and offspring social motivation 61 shared common genetic factors, whereas the intergenerational transmission of neuroticism seemed to be environmentally explained 29 . There was no evidence of an environmental association between parental traits, including anxiety 111 , sociability 110 , and smoking during pregnancy 71 , and offspring personality traits such as sociability and temperament. In addition, an extended twin study found no evidence of environmental transmission or rGE underlying associations between parent and offspring dimensional personality traits 112 .…”
Section: Resultsmentioning
confidence: 88%
“…In addition, an extended twin study found no evidence of environmental transmission or rGE underlying associations between parent and offspring dimensional personality traits 112 . However, two studies observed evocative effects of offspring social behaviours on parenting; adopted offspring’s genetically influenced social behaviours predicted adoptive parent hostility 61 and child-centred parenting 111 . Overall, current and previous literature indicates that relationships between parental factors and offspring personality vary substantially by phenotype, and can involve both genetic and environmental processes.…”
Section: Resultsmentioning
confidence: 99%
“…It is more likely that environmental factors, including parenting, shape this disposition into an anxiety disorder or contribute to the child's resilience to anxiety as demonstrated by adoption studies. 43,44 For the youth in our sample who were at a higherthan-average risk for psychopathology, the importance of parenting may have been particularly strong.…”
Section: Discussionmentioning
confidence: 99%
“…Sociability has been associated with social competence; high levels of sociability are related to high levels of social competence (Rubin, Hymel, & Mills, 1989). GxE for anxiety-related risk has also been found during infancy and toddlerhood, with the association between adoptive father childcentered parenting during infancy and toddler social inhibition moderated by birth mother anxiety symptoms (Brooker et al, 2016). High levels of adoptive father child-centered parenting during infancy were associated with less toddler social inhibition only when birth mother anxiety symptoms were low.…”
Section: The Parent-child Dyadmentioning
confidence: 99%